Geographic distribution of suicide and railway suicide in Belgium, 2008–2013: a principal component analysis. Issue 2 (3rd April 2017) - Strale, Mathieu; Krysinska, Karolina; Overmeiren, Gaëtan Van; Andriessen, Karl
Abstract : This study investigated the geographic distribution of suicide and railway suicide in Belgium over 2008–2013 on local (i.e., district or arrondissement ) level. There were differences in the regional distribution of suicide and railway suicides in Belgium over the study period. Principal component analysis identified three groups of correlations among population variables and socio-economic indicators, such as population density, unemployment, and age group distribution, on two components that helped explaining the variance of railway suicide at a local ( arrondissement ) level. This information is of particular importance to prevent suicides in high-risk areas on the Belgian railway network.